Drosophila Mitf regulates the V-ATPase and the lysosomal-autophagic pathway. Issue 3 (3rd March 2016) - Bouché, Valentina; Espinosa, Alma Perez; Leone, Luigi; Sardiello, Marco; Ballabio, Andrea; Botas, Juan
ABSTRACT: An evolutionarily conserved gene network regulates the expression of genes involved in lysosome biogenesis, autophagy, and lipid metabolism. In mammals, TFEB and other members of the MiTF-TFE family of transcription factors control this network. Here we report that the lysosomal-autophagy pathway is controlled by Mitf gene in Drosophila melanogaster . Mitf is the single MiTF-TFE family member in Drosophila and prior to this work was known only for its function in eye development. We show that Mitf regulates the expression of genes encoding V-ATPase subunits as well as many additional genes involved in the lysosomal-autophagy pathway. Reduction of Mitf function leads to abnormal lysosomes and impairs autophagosome fusion and lipid breakdown during the response to starvation. In contrast, elevated Mitf levels increase the number of lysosomes, autophagosomes and autolysosomes, and decrease the size of lipid droplets. Inhibition of Drosophila MTORC1 induces Mitf translocation to the nucleus, underscoring conserved regulatory mechanisms between Drosophila and mammalian systems. Furthermore, we show Mitf-mediated clearance of cytosolic and nuclear expanded ATXN1 (ataxin 1) in a cellular model of spinocerebellar ataxia type 1 (SCA1). This remarkable observation illustrates the potential of the lysosomal-autophagy system to prevent toxic protein aggregation in both the cytoplasmic and nuclear compartments. We anticipate that the genetics of the Drosophila model and the absence of redundant MIT transcription factors will be exploited to investigate the regulation and function of the lysosomal-autophagy gene network.